PENERAPAN ASAS KESEIMBANGAN BERKONTRAK PADA AKAD PEMBIAYAAN PERBANKAN SYARIAH PERSPEKTIF TEORI HUKUM EKONOMI ISLAM - Taufik Kurrohman Kurrohman (Universitas Pamulang, 2016)
This study describes the principle of balance of contract in the product agreement is the spirit of justice, but in fact why the existing agreement in the agreement of Islamic banking is still the form contract (standard ), which has a tendency loss of meaning in common ( Al - Musawah ), balanced and fair ( Al -Is). Practical level agreements in the banking world shows the imbalance phenomenon can be seen from the various clauses of consumer contracts , in which there are provisions that incriminating debtor. In this study, the method used is normative and empirical research. The study found that the agreement in the form of a standard contract is an agreement that does not meet the principle of balance of contract. The study also found it is necessary to apply the contract impartial mechanism of pre- contract , contract implementation and after the contract runs even in cases of civil disputes under the agreement .